Antepartal & Intrapartal CTG and Correlation with Feto-Maternal Outcome (The Planet, 2022)
Introduction: Cardiotocography (CTG) is a method of graphically (or "graph") recording fetal cardiac activity (also known as "cardio") and uterine contractions (also known as "toco"), both of which are constantly and at the same time scale captured during uterine quiescence and contraction. The scope of the method has now been greatly expanded to include the antenatal period as well, where uterine contraction is not a factor except when it is artificially generated just for the test as in contraction stress test. Although originally designed to monitor the fetus during labor to see how it performs in the face of the circulatory stress brought on by uterine contraction (CST). Aim of the study: The aim of the study was to observe the antepartal and intrapartal CTG findings, and their correlation with fetal and maternal outcomes. Methods: This prospective observational study was undertaken during the period July 2015 to July 2016 at the department of Obstetrics & Gynecology in Azimpur Maternity and Child Health Training Institute. A total of 100 patients were selected for the study and were divided in two equal groups, 50 patients with normal tracing and 50 patients abnormal tracing. Result: Regarding mother age, obstetric traits such gravidity, parity, and gestational age, there was no discernible difference between the normal and abnormal CTG groups. 100% of outcomes were abnormal when a CTG showed bradycardia and no beat-to-beat variability, whereas 72.22% of outcomes were bad when aCTG showed decelerations. While aberrant CTG is not very predictive of abnormal outcomes, normal CTG was more predictive of outcomes that were normal. CTG's sensitivity was greater than its specificity. Conclusion: The most prevalent test for antepartum and intrapartum foetal monitoring is CTG. The clinical influence of cardiotocography on neonatal outcome is still debatable. Further randomized trials with larger sample size are needed to confirm results of the present study.
Keywords: Cardiotocography; Pregnancy; Antepartal; Intrapartal; Fetal